Comparison Among Endoscopic, Laparoscopic, and Open Resection for Relatively Small Gastric Gastrointestinal Stromal Tumors (<5 cm): A Bayesian Network Meta-Analysis - Liu, Zhen; Zeng, Ziyang; Ouyang, Siwen; Zhang, Zimu; Sun, Juan; Wang, Xianze; Ye, Xin; Kang, Weiming; Yu, Jianchun (Frontiers in Oncology, 2021)
Background Endoscopic resection (ESR) is a novel minimally invasive procedure for superficial tumors. Its safety, efficiency, and outcome for gastric gastrointestinal stromal tumors (gGISTs) less than 5 cm remains unclear compared to laparoscopic resection (LAR) and open resection (ONR). The current network meta-analysis aimed to review and analyze the available evidence of this question. Methods PubMed, Embase, Cochrane Library, and Web of Science databases were searched to identify eligible studies published up to July 6, 2020. The perioperative and long-term oncological outcomes among ESR, LAR, and ONR for gGIST (<5 cm) were estimated through the Bayesian network meta-analysis with a random-effect model. Results Fifteen studies with 1,631 patients were included. ESR was associated with a shorter operative time [mean difference, MD: -36; 95% confidence interval, CI (-55, -16)], a higher rate of positive margin [odds ratio, OR: 5.1 × 1010, 95% CI (33, 2.5 × 1032)], and less costs [MD: -1 × 104, 95% CI (-1.6 × 104, -4.4 × 103)] but similar time to resume flatus [MD: 0.52, 95% CI (-0.16, 1.1)] and diet [MD: -3.5, 95% CI (-5.6, -1.6)] compared to LAR. A higher rate of total complications [OR: 11, 95% CI (1.2, 140)] was observed in patients who received ESR compared to patients who received LAR. After excluding perforation from the total complication category, the difference of complication between ESR and LAR disappeared [OR: 0.87, 95% CI (0.22, 2.3)]. The recurrence rate [OR: 1.3, 95% CI (0.40, 4.5)] and disease-free survival [hazard ratio: 1.26, 95% CI (0.60, 2.63)] showed no significant difference between ESR and LAR. ESR was associated with better or equivalent perioperative and long-term outcomes compared to ONR, except for positive margin. A subgroup analysis (<2 and 2–5 cm) showed no significantly different results among these three procedures either. Conclusion ESR was shown to be a safe and efficient alternative procedure to both LAR and ONR for gGISTs less than 2 cm and within 2–5 cm, respectively, without worsening the oncologic outcomes. However, preoperative assessment of tumor site is of importance for the determination of procedures regarding the increased incidence of a positive margin related to ESR.